GREEN LIBRARY MENINGKATKAN KINERJA DAN GAYA HIDUP SEHAT DI LINGKUNGAN KAMPUS - Isnaini Syamsiati (Jurnal Pustakawan Indonesia, 2018)
The comfort and condusive ambience directly propotional to effective ness performance at work. The harmony of life (life balance between human and an environment) needed to reach the real happiness and make confortable of working. Back to nature is the power of movement present natural ambience in the office to decrease of depression and saturation point. Many people ignore about an environment, either in their house of their office. Have we did of 5R tagline (resik, rapi, ringkas, rawat, rajin) have we realized and took care if our body is machine to our daily activity? Apparently, mental condition and natural an environment to have influence on health, mindset, and effectivity of work. Green library is pioneer to create “paradise” ambience present healthy life, confortable zone, and condusive work to civitas academica. The harmony between human and an environment become a strong and possitive energy for all.